Autosomal hypophosphataemic bone disease responds to 1, 25-(OH)2D3. Issue 3 (March 1981) - Scriver, C R; Reade, T; Halal, F; Costa, T; Cole, D E
Abstract : We diagnosed non X-linked hypophosphataemic bone disease in a 38-month-old girl. Findings included: genu varum, shortened stature, fasting hypophosphataemia (2.3-2.5 mg/100 ml; 0.74-0.81 mmol/l), diminished theoretical renal threshold for phosphate (TmP/GFR), and osteomalacia without rickets. One patient (the father) had fasting hypophosphataemia (2.3-2.7 mg/100 ml; 0.74-0.87 mmol/l) and low TmP/GFR without osteomalacia or shortened stature. Treatment of the girl with 1, 25-(OH)2D3 (1 microgram a day) raised the level of serum phosphorus, improved tubular reabsorption of phosphate, and healed the bone deformity; this combination of responses is not present in X-linked hypophosphataemia. There was no correction of hypophosphataemia or TmP/GFR with 1, 25-(OH)2D3 treatment (1-3 micrograms a day) in the father.